Equity and Equality of Inclusive Education - Hina Fazil,Rabia Hashmi (JIE, 2024)
Human Rights Commission (2007) declared Article 2 that every individual has equal rights to education and access to human rights without distinction of race, color, sex, language, religion, political, national or social origin, property birth, or another status. Klinefelter syndrome (gender disorder), also known as Transgender (commonly named third gender or Khusra in Pakistan), is not considered human beings in our society.